Comparative Studies on the Interaction of Cochinchinenin A and Loureirin B with Bovine Serum Albumin - Tianming Yang; Hao Zhang; Haiyan Fu; Yuanbin She; Can Huang; Yan Hu; Liping Wang (Journal of Spectroscopy)
This paper describes the simple, sensitive, and effective spectrophotometric methods based on ultraviolet, fluorescence and circular dichroism for revealing the interactional mechanism of Cochinchinenin A (CA) and Loureirin B (LB) with bovine serum albumin (BSA). Under simulated physiological conditions, it was demonstrated that the fluorescence quenching mechanisms between CA (or LB) and BSA as a static quenching mode, or a combined quenching (dynamic and static quenching) mode were related to concentration level of CA (or LB). The binding distance (rCA, rLB) and the quenching efficiency (KSV), especially for the binding constants value of ligands to BSA, were affected by the methoxyl group at position 4 at different temperatures. The corresponding thermodynamic parameters were also obtained and indicated that electrostatic forces play a major role in the formation of the LB-BSA complex, but probably a combined force for CA-BSA complex. Furthermore, synchronous fluorescence spectroscopy and circular dichroism spectra demonstrated that the secondary structures of BSA were changed to varying degrees by the binding of CA (or LB).